IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR: KAJIAN LITERATUR - Ryanjani Lila Anggraita; Fitri Puji Rahmawati; Anik Ghufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the implementation of the independent curriculum implementation in elementary schools. This research uses the SLR (Systematic Literature Review) research method, SLR (Systematic Literature Review) is a method used to refer to certain research methodologies and developments carried out by collecting and evaluating research related to the focus of a particular topic. Data collection both from journal articles, books, proceedings, and other accessible articles. The articles reviewed came from Publish and Parish from 2017 to 2024. The purpose of SLR is to analyze, find, review, and interpret previous research on the implementation of the independent curriculum implementation in primary schools. In this study, 200 relevant articles were found and then filtered based on the inclusion criteria, resulting in 15 articles used for the primary study. The results of this study provide insight that the independent curriculum has been implemented and implemented in elementary schools. And the implementation of this independent curriculum is effective in improving knowledge and skills, because in the independent curriculum there are project activities that can improve character, namely the character contained in the Pancasila student profile. In implementing the independent curriculum, there are several obstacles that come from the teacher factor. However, these obstacles can be minimized in various ways, namely teachers getting training on the independent curriculum, cooperation and coordination of all parties involved, and involving teachers in curriculum development.